Effect of transcranial direct current stimulation on postpartum depression: A study protocol for a randomized controlled trial - Sun, Weiming; Kang, Xizhen; Dong, Xiangli; Zeng, Zijian; Zou, Qing; Su, Meixiang; Zhang, Ke; Liu, Guanxiu; Yu, Guohua (Frontiers in Psychology, 2023)
Postpartum depression (PPD) is a complex combination of physiological, emotional, and behavioral alterations associated with postpartum chemical, social, and psychological variations. It does harm to the relationship between family members that could potentially last for years. However, standard depression treatments are not ideal for PPD, and the outcomes of these treatments are debatable. Transcranial direct current stimulation (tDCS) is an emerging technology that could provide patients with PPD with a safe and non-pharmacological treatment. tDCS can relieve depression by directly stimulating the prefrontal cortex through the excitatory effect of the anode. It may also ease depression indirectly by promoting the production and release of the neurotransmitter GABA. The mechanism of tDCS makes it an ideal therapeutic approach to treat PPD, although it has not been widely used, and its effect has not been evaluated systematically and effectively. A double-blind, randomized controlled trial will be conducted involving 240 tDCS-naive patients with PPD, who will be randomly divided into two groups. One group will receive routine clinical treatment and care with active tDCS, and the other group will receive routine clinical treatment and care with sham tDCS. Each group of patients will receive a 3-week intervention during which they will receive 20 min of active or sham tDCS 6 days per week. The Montgomery–Åsberg Depression Rating Scale will be administered before the intervention as a baseline and on each weekend throughout the intervention phase. Before and after the intervention, the Perceived Stress Scale and the Positive and Negative Affect Schedule will be evaluated. Side effects and abnormal reactions will be recorded during each treatment. As antidepressants are banned in the study, the results will not be affected by drugs and will therefore be more accurate. Nonetheless, this experiment will be conducted in a single center as a small sample experiment. Therefore, future studies are required to confirm the effectiveness of tDCS in treating PPD.